From confession to creed: Nicaea and the ecclesial dialectic between movement and institution - Conradie, Ernst M. (Stellenbosch Theological Journal, 2026)
This contribution to “Receiving Nicaea” in 2025, within the South African context, examines the dialectic between confession and creed, specifically the act of confession and its corresponding creedal formulations. Its “theoretical framework” is provided by a similar dialectic between movement and institution in the works of Henri Bergson, H. Richard Niebuhr, and David Bosch. This raises the question of how a creative tension between movement and institution can be kept alive. This depends on how both the movement (here, the anti-imperial movement of the Spirit) and the institution (here, the church as God’s covenant partner) are understood. The danger of not maintaining such a creative tension is illustrated with the example of the reception of the Confession of Belhar. On this basis, the basic structure of the Nicene Creed (as revised at Constantinople, 381) is explored, given its Trinitarian logic and its narrative framework. It is argued that despite its imperial setting and purpose, the Nicene Creed may be read as a critique of Empire. It is this impulse that can ensure that the dialectic between movement and institution, between the body of Christ and the mission of the Spirit, is kept alive.